The impact of comorbidities on outcome of patients admitted with Coronavirus disease 2019 infected at Pietersburg Hospital, Polokwane, Limpopo Province - Moabelo, Koena Johannes (My University, 2025)
Background: The emergence of the novel Coronavirus disease 2019 (COVID-19), causative agent identified as severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2), in late 2019 in Wuhan City, has led to a global outbreak of COVID-19 culminating in the declaration of a pandemic by the World Health Organization (WHO). As of 2nd of October 2022, the cumulative number of cases have reached the 600 million mark, with just over 6.5 million deaths reported to WHO. Purpose: To determine the relationship between comorbidities and adverse outcome in patients admitted with COVID-19 infection at Pietersburg Hospital from March 2020 to March 2021. Methods: This was a retrospective study using secondary data extracted from DATCOV portal, a web-based disease surveillance system of patients admitted with laboratory-confirmed SARS-CoV-2 PCR results. Variables extracted from the portal include demographics and clinical data such as comorbidities, management strategies and adverse outcomes (need for oxygenation, organ failure, admission to high care or intensive care unit (ICU) and death). Data was analysed using SSPS 27.0. Variables were presented as numbers, percentages and cross-tabulations. Results: There were 446 eligible study participants, 225(50.4%) were females and 221(49,6%) were males, and 311(70%) had comorbidities. The median age of patients was 57 (13-96) years. The most prevalent comorbidity was hypertension in 208 patients (46%) followed by diabetes in 153 patients (34%).Both hypertension and diabetes largely contributed to the reported adverse outcome of death. A total of 159 (36%) deaths related to COVID-19 infection were reported during the study period. Using the logistic regression model, the odds of non-survival were significantly associated with two variables, age and ward setting. An increase in patient’s age by 1 year, increased the odds of dying by 1.09 as compared to being alive (OR 1.094, 95% CI: 1.038-1.153, p-value<0.001). Being admitted to intensive care unit (ICU) was associated with a higher death rate ( OR 0.020, 95% CI: 0.001-0.292, p-value 0.004). Conclusion: Hypertension and diabetes (p-values of 0.020 and 0.009 respectively) appeared to be significantly related to patient’s adverse outcome of non-survival, with hypertension being the common factor in all deaths reported.
Thesis (M. Med. (Internal Medicine)) -- University of Limpopo, 2025
Keywords: Covid-19; SARS-CoV-2; Comorbidities; Adverse outcome; COVID-19 (Disease); Coronavirus infections; Comorbidity; Hypertension; Diabetes